UX evaluation of IoT-based applications for Smart Cities: a rapid systematic review - Choma, Joelma; Zaina, Luciana (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE); 2024: Anais do XXVII Congresso Ibero-Americano em Engenharia de Software, 2024)
The development of systems based on the Internet of Things (IoT) technologies is becoming increasingly popular in the context of Smart Cities. Recent research in Software Engineering (SE) has investigated the characteristics of these systems and the most appropriate approaches to their design and development. IoT-based applications are strongly characterized by the interaction among multiple devices, users, and services. These characteristics make these applications complex and difficult to evaluate, particularly in terms of User Experience (UX) design. In this study, we performed a rapid systematic review to examine the methods and practices commonly employed for evaluating the UX of IoT-based applications for Smart Cities. We analyzed 43 studies covering different types of IoT-based applications, most in the area of Smart Home. Our findings indicate that user testing questionnaire-based (e.g., SUS - System Usability Scale and UEQ - User Experience Questionnaire) and interviews are the most used methods to evaluate IoT applications, while few studies mentioned user testing based on automated measurement or expert-based reviews. This work contributes to SE research by revealing the need to explore UX evaluation methods based on usage data and the combination of methods for continuous UX evaluation in the context of IoT and Smart Cities.